PARENTS COMMUNICATION PATTERNS TOWARDS CHILDREN WITH MENTAL DISORDERS - Hisan, Khairatun; Muzakkir, Muzakkir; Fitriyani, Fitriyani (Jurnal Sosiologi Dialektika Sosial, 2024)
Communication is a necessity or means of social interaction for human life. However, some individuals, such as mentally retarded children, experience difficulties in communicating due to various factors and environments. This study aims to understand the communication patterns used by parents in interacting with children who suffer from mental retardation. The method used is Systematic Literature Review to explore insights into parents' communication patterns towards mentally retarded children. The researcher collected, summarized, evaluated, interpreted and synthesized information from journals published between 2019-2024. The results showed that communication patterns used by parents can affect learning outcomes and behavioral changes in children with mental retardation. The ideal communication pattern is interpersonal communication that involves direct interaction and feedback between parents and children. Parents need to have extra patience in communicating with mentally retarded children, and communication must be done regularly so that communication development for children can run well. Based on the author's understanding, interpretation and evaluation of various existing journals, it turns out that the communication pattern most favored by mentally retarded children is through audio and video-based multimedia interactive media and gross and fine motor skills through the puzzle game method.